2015
DOI: 10.18052/www.scipress.com/ilshs.56.127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Period of Aquatic Therapy Exercise on the Quality of Life and Depression in Aged Males Suffering from Chronic Physical Pains

Abstract: ABSTRACT. Aging is a stage of life that increases the risk of physical diseases, some of which are chronic and can affect different dimensions of life's quality and the status of psychological factors in these patients. In addition to medical supports, it is essential to provide sport complexes in accordance with the physical and mental condition of these patients. The aim of this study was to evaluate the effect of a period of aquatic therapy exercise on the quality of life and depression in aged males suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Khanjari et. al (39), in analyzing the effect of a period of aquatic therapy exercise on the quality of life and depression in aged males suffering from chronic physical pains showed that exercise in water created a meaningful promotion in pain scale, life quality and depression. But Lund et.…”
Section: Introductionmentioning
confidence: 99%
“…Khanjari et. al (39), in analyzing the effect of a period of aquatic therapy exercise on the quality of life and depression in aged males suffering from chronic physical pains showed that exercise in water created a meaningful promotion in pain scale, life quality and depression. But Lund et.…”
Section: Introductionmentioning
confidence: 99%